Time- and Site-Dependent Postmortem Redistribution of Antidepressants and Neuroleptics in Blood and Alternative Matrices. Issue 4 (22nd July 2020) - Brockbals, Lana; Staeheli, Sandra N; Gascho, Dominic; Ebert, Lars C; Kraemer, Thomas; Steuer, Andrea E
Abstract: Postmortem redistribution (PMR) leads to challenges in postmortem case interpretation. Particularly antidepressants and neuroleptics are expected to undergo PMR based on their physico-chemical properties. For the current study, time- and site-dependent PMR of 20 antidepressants and neuroleptics were investigated in humans (authentic cases); five of which are discussed in detail (citalopram, mirtazapine, quetiapine, risperidone and venlafaxine) along with two metabolites (9-OH-risperidone and O-desmethylvenlafaxine). Blood [femoral (pB) and heart blood (HB)] and tissue biopsy samples (lung, kidney, liver, spleen, thigh muscle and adipose tissue) were collected upon admission to the institute utilizing a computed tomography-guided sample collection workflow (t1). Approximately 24 h later (t2; mean 23 ± 9.3 h), samples from the same body regions were collected manually. Liquid chromatography–tandem mass spectrometry was used for quantification. Most antidepressants and neuroleptics showed significant time-dependent concentration changes indicating the occurrence of PMR. For the first time, two phases of redistribution in pB for quetiapine were proposed (concentration decreases in the early postmortem phase, followed by concentration increases) and contrasting existing literature, both concentration increases and decreases in pB overtime were observed for risperidone and 9-OH-risperidone. Venlafaxine and its metabolite only showed minimal concentration changes, while citalopram exhibited a trend for concentration increases and mirtazapine for concentration decreases in pB overtime. Based on time-dependent tissue data, passive diffusion processes along the muscle-to-pB, liver-to-HB and lung-to-HB concentration gradients could be proposed along with bacterial degradation. Overall, no case interpretation had to be adjusted, which suggests that PMR changes of antidepressants and neuroleptics do not seem to be relevant for forensic case interpretation within the 24 h period that was investigated. However, limitations of the current study (e.g., temperature-controlled storage of the bodies) could have led to an underestimation of occurring postmortem changes, hence, interpretation of postmortem results should always be conducted with care, considering PMR phenomena and inter-individual variability.